Improvement and use of laboratory methods for toxicological assessments on eusocial bees - Tomé, Hudson Vaner Ventura (Universidade Federal de Viçosa, 2015)
The importance of bees for pollination is unquestionable. Nevertheless, populations of these organisms have suffered considerable reductions in the world by several factors including the use of pesticides. Eusocial bees usually live in nests, where part of the post-embryonic development occurs in closed combs, what makes difficult the study of bee development. Therefore, to study the impact of these pesticides without interference from environmental factors, the rearing of these organisms under controlled conditions in laboratory is necessary whereas part of pesticide exposure occurs via larval feeding in natural conditions. In this sense, the improvement of rearing methods can contribute to the understanding of how pesticides affect morphophysiological and molecular processes in bees by exposure of larvae to these compounds. This work aimed to develop and/or improve in vitro bee rearing techniques and perform toxicological tests to assess brain and behavioral plasticity in stingless bees. In addition, disorders caused by pesticides in stingless bees and honeybees were also studied. In general, it can be concluded that: 1) the rearing of stingless M. quadrifasciata laboratory de reased de elop e t of so e ees’ rai regio s compared with bees kept in natural conditions; 2) the synthetic insecticide imidacloprid and bio-insecticide spinosad are highly toxic to stingless M. quadrifasciata and also promote sublethal effects on workers of this species; 3) the mortality of Apis mellifera reared in vitro can be greatly reduced by using procedures described in the present study and 4) all pesticides tested caused mortality and sublethal effects (reductions in body weight, changes in gene activity associated with detoxification, developmental disorders and structures of the antennas) in honey bees after exposure during the larval stage to realistic field pesticide concentrations.

A importância das abelhas para a polinização é inquestionável. Apesar disso, populações desses organismos têm sofrido consideráveis reduções no mundo por diversos fatores que incluem o uso de pesticidas. Abelhas eussociais geralmente vivem em ninhos, onde parte do desenvolvimento pós-embrionário ocorre em favos fechados, constituindo empecilho para o estudo do desenvolvimento. Portanto, para se estudar o efeito de pesticidas nesses organismos sem interferência de fatores ambientais é necessário a criação em condições controladas em laboratório, sendo que em condições naturais parte da exposição a pesticidas ocorre via alimentação larval. Nesse sentido, o aprimoramento de métodos de criação pode contribuir para o entendimento de como pesticidas afetam processos morfofisiológicos e moleculares nas abelhas mediante exposição das larvas a esses compostos. A presente tese objetivou desenvolver e/ou melhorar técnicas de criação de abelhas in vitro e realizar testes toxicológicos para avaliar a plasticidade cerebral e comportamental em abelhas sem ferrão. Além disso, desordens ocasionadas por pesticidas em abelhas sem ferrão e abelhas melíferas também foram estudadas. De maneira geral, os resultados obtidos na presente tese permitiram concluir que: 1) a criação de abelha sem ferrão M. quadrifasciata em laboratório retarda o desenvolvimento de algumas regiões cerebrais em relação às abelhas mantidas em condições naturais; 2) o inseticida sintético imidaclopride e o bioinseticida spinosade são altamente tóxicos a abelha sem ferrão M. quadrifasciata e também promovem efeitos subletais em operárias dessa espécie; 3) é possível reduzir consideravelmente a mortalidade de Apis mellifera criadas in vitro mediante o uso de procedimentos descritos de forma inédita no presente estudo e 4) todos os pesticidas causaram mortalidade e efeitos subletais (reduções no peso corporal, alterações na atividade de genes associados a destoxificação, distúrbios no desenvolvimento e estruturas das antenas) em abelhas melíferas em virtude da exposição de concentrações realistas de campo durante a fase larval.
Plasticidade cerebral e comportamental e danos múltiplos de pesticidas em abelhas eussociais
Keywords: Abelhas - Criação; Apis mellifera; Melipona quadrifasciata; Pesticida - Toxicologia; Entomologia Agrícola